PERAN DAN FUNGSI DPD RI DALAM RANGKA MENUJU SISTEM BIKAMERAL YANG EFEKTIF MELALUI AMANDEMEN UUD 1945 KE-5 - Wahyu Widodo (Jurnal Pembaharuan Hukum, 2014)
An important aspect in the process of Indonesia's transition to democracy is in the field of constitutional reforms set out in the 1945 Constitution amendment One of the important change is in the form of a new state agency called the Regional Representative Council (DPD). Since the amendment, Indonesian parliamentary system has changed from a system of unicameral to a bicameral system. Manifestations of this institution has awakened hope that the local community problems of the region can be fought at the national level. However, if the note functions, powers and duties set out in Article 22 D the 1945 Constitution and Act 22 of 2003 concerning the composition and position of the MPR, Parliament, DPD and local parliament, then raised a lot of assumptions that are functions of the Regional Representative Council can represent regional interests. DPD is not only serves as a counseling board autonomy, does not serve as the country's legislature adopts a bicameral. Amendments to the Constitution of 1945 is the main road to strengthen the position of this institution as the legislature to assist the Parliament.